Gender in contemporary Italian context. A focus on informal education and proposals for a gender sensitive approach through intergenerational and intercultural dimensions - Lisa Brambilla; Giulia Pozzebon; Marialisa Rizzo (Ex Aequo: Revista da Associação Portuguesa de Estudos sobre as Mulheres)
Gender is a pervasive informal educational experience. This is particularly true in the Italian context, where the educational system, lacking an intentional gender education and a gender-sensitive approach, risks to contradict its most essential finalities: the promotion of equal opportunities and active citizenship. This paper, according with the transformative vocation of pedagogical research, explores the risks and opportunities of informal gender education. After a theoretical introduction, intergenerationality and interculturality are suggested as dimensions whose exploration facilitates a better understanding of the complexity of the contemporary gender order, opening up new possibilities to challenge it.